2016
DOI: 10.1007/s40242-016-5383-4
|View full text |Cite
|
Sign up to set email alerts
|

Shape-controlled synthesis of Fe3O4 nanocrystals with incontinuous multicavities

Abstract: In the solvothermal synthesis process, the effect of NaOH dosages of from 0.3 g to 4.0 g on the morphology evolution(from nanoparticles to octahedra) of Fe 3 O 4 crystals was carefully investigated. Meanwhile, the growth process of Fe 3 O 4 crystals at different reaction time was also investigated. Furthermore, it has been found that the particle size and crystallinity of Fe 3 O 4 crystals can be controlled by the dosages of NaOH. In this paper, the increases of both the reaction time and the NaOH concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[13,14] Meanwhile, the hierarchical nanostructure may buffer the strain change during the charge/discharge processes and alleviate the pulverization of the electrode material, which would facilitate the electrochemical performances. [15,16] Various hierarchical nanostructures of electrode materials have been designed to enhance the electrochemical performances, such as nanocrystal/nanoparticle, [17][18][19][20] nanofiber/nanorod, [19][20][21] hierarchical nanoflower, [22][23][24] etc. To the best of our knowledge, the good cycling stability of CoF 2 used as high capacity cathode materials has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Meanwhile, the hierarchical nanostructure may buffer the strain change during the charge/discharge processes and alleviate the pulverization of the electrode material, which would facilitate the electrochemical performances. [15,16] Various hierarchical nanostructures of electrode materials have been designed to enhance the electrochemical performances, such as nanocrystal/nanoparticle, [17][18][19][20] nanofiber/nanorod, [19][20][21] hierarchical nanoflower, [22][23][24] etc. To the best of our knowledge, the good cycling stability of CoF 2 used as high capacity cathode materials has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, N-doped GDY and its derivatives with outstanding advantages have been extensively studied in the energy conversion and storage, biological application, and environmental protection. [57][58][59] Given the influence of structures on the properties of GDY, a great deal of works including post-heating method and top-down method have been devoted into the fabrication of N-doped GDY and its derivatives. The post-heating method refers to the synthetic process of Ndoped GDY by heating GDY under N sources, such as high-purity ammonia.…”
Section: Metal-free Based Gdymentioning
confidence: 99%
“…As the N atom has a suitable atomic size but higher electronegativity than that of the C atom, N atoms can be doped into the structure of GDY for the effective regulation of their basic properties. Thus, N‐doped GDY and its derivatives with outstanding advantages have been extensively studied in the energy conversion and storage, biological application, and environmental protection 57–59 . Given the influence of structures on the properties of GDY, a great deal of works including post‐heating method and top‐down method have been devoted into the fabrication of N‐doped GDY and its derivatives.…”
Section: Design and Synthesis Of Gdymentioning
confidence: 99%
“…Frank et al [7] presented flow of bubble train in non-Newtonian fluids. Zhan et al [8] reported the hydrodynamic behaviour of tapered slurry bubble column with the angle 1.91 o and height 3 m. The effects of operating parameters on the flow regime, gas holdup and pressure drop were investigated. Chandarkar et al [9] studied the gas dispersion behaviour in non-Newtonian liquid in vertical upflow bubble column.…”
Section: Introductionmentioning
confidence: 99%